Role of salicylic acid as foliar spray on hydride rice (BRRI Hybrid dhan3) cultivation in Bangladesh - Issak, Mohammad; Khatun, Most Moslama; Sultana, Amena (Research in Agriculture Livestock and Fisheries, 2017)
The experiment was conducted to study the effect of salicylic acid (SA) as foliar spray on yield and yield contributing characters of BRRI Hybrid dhan3.The experiment was laid out in a randomized complete block design (RCBD) with three replications and six treatment combinations as, T1: 0 μM SA, T2: 200 μM SA, T3: 400 μM SA, T4: 600 μM SA, T5: 800 μM SA and T6: 1000 μM SA. The results revealed that biomass production, dry matter production and yield and yield contributing characters were significantly increased due to the foliar application of SA. At the maximum tillering (MT) stage, the highest biomass production (15.0 t/ha) and dry matter production was observed in T3 treatment. Treatments T4, T5 and T6 showed significant variation on the effective tillers/hill. The maximum effective tillers/hill were found in the treatment T6. The percentages of spikelet sterility were decreased with increasing the level of SA and the percentage of filled grains/panicle were increased with increasing level of SA. The insect infestation was reduced with increasing level of SA to up to 1000 μM. The maximum grain yield (9.21 t/ha) and straw yield (9.22 t/ha) was found in the treatment T6 which was identical to T5. On the other hand, in all cases the lowest results were found in the control treatment. The result showed that grain yield of rice increased with increasing level of SA to up to 1000 μM (T6 treatment). Our results suggest that foliar spray of SA might be applied to increase the yield of hybrid rice in Bangladesh. Res. Agric., Livest. Fish.4(3): 157-164, December 2017